Manajemen Kurikulum Pesantren Berbasis Madrasah di MAN 3 Sleman Yogyakarta - Tsuroyya, Elfa (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
This research aims to know the management of curriculum at an Islamic boarding school, that is madrasa based.  This research focuses on the factors that restricting and supporting in developing the curriculum of pesantren, as well as on its problem solving. Using qualitative approach, this research gathered the data through interviews, observation and documentation. The results showed that the management of curriculum development designed by PP. Muntasyirul Ulum MAN 3 Sleman, Yogyakarta include planning, organizing, implementing and evaluation. Curriculum development strategies were carried out by carrying out these steps: 1) Bench marking, 2) scientific visit, 3) trial and error program, 4) establishment of curriculum commission, 5) review process, open criticism and suggestions, and 6) evaluation during the end of the semester.